Implementasi Program Pustaka Bergilir Di Daerah Tertinggal [Implementation of Rotating Library in Disadvantaged Regions] - Annas Firdausi (Jurnal AKRAB, 2019)
Preliminary. Disadvantaged Districts in Indonesia generally have a quality of human resources below the national average. This can be seen from the low average Human Development Index (HDI) in disadvantaged areas. Program Pustaka Bergilir – Buku Masuk Rumah in the village is one of the solutions to overcome the limitations of regional income and expenditure, overcoming geographical constraints, cost and time constraints, because the Village Government has the financial freedom to allocate budgets in the library and literacy fields. Method. The study was conducted qualitatively by utilizing secondary data sources obtained from official publications of agencies / institutions, applicable legislation, and other related publications. Results and Discussion. Village Government has a strong legal basis for allocating budgets for the development and management of village libraries and reading parks. Implementation of Program Pustaka Bergilir – Buku Masuk Rumah is easier, because Village Government is closer to the community, so it is easier to reach people and promote the importance of literacy and reading interest to improve the quality of human resources, especially in disadvantaged areas. Some of the obstacles that may be faced in the implementation of the program are the low commitment of the village government, weak human resources in the village and the district, operational constraints, and the low interest of the community. However, all of this can be overcome by a variety of innovative and collaborative programs that involve all stakeholders, such as donation programs, cooperation, promotions and publications, and literacy actions. ABSTRAK Pendahuluan. Kabupaten Daerah Tertinggal di Indonesia umumnya memiliki kualitas sumber daya manusia di bawah rata-rata nasional. Hal ini terlihat dari rendahnya rata-rata Indeks Pembangunan Manusia (IPM) di daerah tertinggal. Program Pustaka Bergilir – Buku Masuk Rumah di desa menjadi salah satu solusi untuk mengatasi keterbatasan anggaran pendapatan dan belanja daerah, mengatasi kendala geografis, kendala biaya maupun waktu, karena Pemerintah Desa memiliki keleluasaan secara finansial untuk mengalokasikan anggaran di bidang perpustakaan dan literasi. Metode. Penelitian dilakukan secara kualitatif dengan memanfaatkan sumber data sekunder yang diperoleh dari publikasi resmi instansi/lembaga, aturan perundang-undangan yang berlaku, dan publikasi terkait lainnya. Hasil dan Pembahasan. Pemerintah Desa memiliki landasan hukum yang kuat untuk mengalokasikan anggaran bagi pengembangan dan pengelolaan perpustakaan dan taman bacaan milik desa. Implementasi Program Pustaka Bergilir – Buku Masuk Rumah menjadi lebih mudah, karena Pemerintah Desa lebih dekat dengan masyarakat, sehingga lebih mudah menjangkau masyarakat dan mensosialisasikan pentingnya literasi dan minat baca untuk meningkatkan kualitas sumber daya manusia, terutama di daerah tertinggal. Beberapa kendala yang mungkin dihadapi dalam implementasi program adalah rendahnya komitmen pemerintah desa, lemahnya SDM di desa maupun di kabupaten, kendala operasional, dan rendahnya minat masyarakat. Namun, semua ini dapat diatasi dengan berbagai program inovatif dan kolaboratif yang melibatkan seluruh stakeholders, seperti program donasi, kerjasama, promosi dan publikasi, maupun aksi literasi.